Framing conflict through euphemism and dysphemism in Southeast Asian and Middle Eastern media - Rohmatullah, Muhammad Ali; Degaf, Agwin (JOALL (Journal of Applied Linguistics and Literature), 2025)
The Israel-Hamas conflict, claiming around 42,960 lives from October 2023 to September 2024, has received extensive international media attention with varying portrayals. While Western perspectives are widely examined, research on non-Western media remains limited. This study analyzes how Channel News Asia (CNA) in Southeast Asia and The National in the Middle East employ euphemism and dysphemism to frame public perceptions of the conflict. Using Allan and Burridge’s typologies, this qualitative research examines 20 news articles from each outlet between October 2023 and September 2024. Through coding and categorization, it explores how language not only reports events but also shapes national and international discourse. Results reveal a significant difference in rhetorical approach: CNA predominantly uses dysphemisms, particularly to delegitimize Hamas, positioning the group as a threat. to state and represent a very bad thing or condition. In contrast, The National employs more euphemisms to soften portrayals of Palestinian actions and emphasize humanitarian concerns, presenting Palestinians sympathetically and highlighting civilian impact. This strategy suggests alignment with pro-Palestinian narratives, aiming to evoke empathy from readers. This study contributes to media discourse analysis by examining non-Western framing of conflict, illustrating how euphemisms and dysphemisms act as ideological tools in shaping public opinion. Expanding the scope to include non-Western perspectives highlights the role of regional media in influencing global narratives on sensitive geopolitical issues. Future research could apply this framework to similar rhetorical strategies in other conflicts and contexts.